Pergulatan Identitas Diaspora Komunitas Toraja- Kristen di Tawau Malaysia - Dase, Admadi Balloara; Nallo, Nober (Universitas Negeri Medan, 2024)
This research examines the identity struggles of the Toraja diaspora in Sabah Malaysia. The Toraja diaspora in Malaysia is a minority group in Tawau City, Sabah Malaysia. Malaysia as a Muslim-majority country imposes many Muslim rules. Therefore, the author examines how the minority Toraja diaspora community grapples with its identity as a Toraja tribe from Indonesia and Christian in Tawau City. This research uses qualitative research methods through field and literature studies using the New Ethnography perspective. The author uses Stuart Hall's concept of cultural identity to show how identity formation occurs because of two things. First, there is an interpretation of the same history and culture. Second, how the community negotiates with other groups. The author found that the Torajans have a community base in the Anglican and Basel Churches in Tawau. The Anglican Church is the first church that the Toraja community belongs to, but does not accept when Torajans perform rites at death ceremonies in this case badong because it is considered an idol. Meanwhile, the Basel Church opens space for Torajans to perform their cultural rites such as mantunu and ma' badong. Torajans also use Torajan symbols in worship as an image of cultural roots. The similarities and historical roots sparked the Toraja people in Tawau to join the Anglican Church and the Basel Church.